Time to death among HIV-infected under-five children after initiation of anti-retroviral therapy and its predictors in Oromiya liyu zone, Amhara region, Ethiopia: a retrospective cohort study - Bereka Tefera Marie; Weldemariam Sintayehu Argaw; Bitewa Yibelu Bazezew (BMC, 2022)
Abstract Background Human Immunodeficiency Virus (HIV) is infection which mainly attacks immune system of an individual. Its disease progress is rapid in children and if treatment is not initiated nearly half of infected children will die by the second year of infection. In Ethiopia, nearly twenty four percent of HIV related death is happen to under-five children; however studies done in this specific age group are limited are with poor evidence of predictors. Objectives To determine time to death and identify predictors of death in HIV infected under- five children on antiretroviral therapy in Amhara regional state, Oromia 'liyu' zone, Northeast Ethiopia, from 2014 to 2019. Methods Institution based retrospective follow up study was conducted in 376 under-five HIV- infected children on antiretroviral therapy from January 2014 to December 2019 in health institutions in Oromia Liyu Zone, Amhara region, Ethiopia. Multivariable Cox-proportional hazard regression model was used to identify independent predictors of mortality in HIV- infected under-five children on antiretroviral therapy. Result At the end of follow up, 304 (80.85%) of HIV-infected children were alive, 39 (10.95%) were lost to follow up, 12 (3.19%) were transferred out and 21 (5.59%) were reported dead due to HIV/AIDS. The cumulative survival probabilities of children after 3, 6, 12, 24 and 36 months were 0.99, 0.98, 0.97, 0.89 and 0.87 respectively. The overall mean time to death was 19.7 months (95%CI = 18.74-20.67) with incidence of 5.9 deaths per 100 child-months (95%CI: 3.89-9.09). Children with severe malnutrition at baseline (AHR = 4.9; 95 CI: 1.04, 23.50), advanced WHO clinical stage at enrolment (AHR = 3.9; CI: 1.37, 10.88), poor adherence to ART (AHR = 6.56; CI: 3.33, 10.14) and with no history of Isoniazide prophylaxis were significantly associated to higher mortality events (AHR = 3.6; CI: 1.24, 10.18). Conclusion Death of HIV-infected under-five children on ART is high within the first one year after enrolment. The risk of death increased if the child was malnourished at beginning of treatment, had poor ART adherence, with advanced WHO clinical stages and lack of Isoniazide prophylaxis during their age of infancy.